Modeling Community Participation Transformation In Educational Service Implementation In The Ha-Anim Ecological Region, Asmat Regency, South Papua Province - Yohannes Rahail (Eduvest - Journal of Universal Studies, 2026)
The provision of educational services in the Ha-Anim ecological region in Asmat Regency South Papua Province, faces various complex challenges, including limited resources, difficult geographical conditions and low community participation in supporting educational services. So far, community participation has tended to be passive and symbolic, thus failing to make a real contribution to improving the quality and sustainability of education. Based on these conditions, this study aims to examine a relevant community participation transformation model to strengthen the governance of education services based on local wisdom, inclusiveness and sustainability. This study uses a descriptive qualitative approach with purposive sampling techniques to determine informants from two districts in Asmat Regency, namely Agats District (urban area) and Ayam District (rural area). The informants consisted of local stakeholders representing the 3-Tungku elements (traditional leaders, religious leaders and village government) and the 2-Peran elements (female leaders and youth leaders). Data collection was conducted through in-depth interviews and Focus Group Discussions (FGD), while data analysis consisted of three main stages, namely: (1) identification of primary and secondary data, (2) categorization of data according to research themes, and (3) interpretation and analysis of results based on qualitative research principles. The results of the study show that the transformation of community participation in Asmat needs to be directed towards a paradigm shift from formal participation to substantive participation. Revitalizing school committees is a key strategy through the integration of local social elements, namely traditional leaders, religious leaders, women and youth as representatives of the community.